LASIK surgery of granular corneal dystrophy type 2 patients leads to accumulation and differential proteolytic processing of transforming growth factor beta‐induced protein (TGFBIp). Issue 3 (3rd January 2016) - Poulsen, Ebbe Toftgaard; Nielsen, Nadia Sukusu; Jensen, Morten M.; Nielsen, Esben; Hjortdal, Jesper; Kim, Eung Kweon; Enghild, Jan J.
Abstract : More than 60 mutations in transforming growth factor beta‐induced protein (TGFBIp) have been reported in humans causing a variety of phenotypic protein aggregates in the cornea, commonly termed corneal dystrophies. One mutation, generating an arginine to histidine amino acid substitution at position 124 in mature TGFBIp leads to granular corneal dystrophy type 2 (GCD2). Homozygous GCD2 cases develop massive protein accumulation early in life whereas heterozygous GCD2 cases become affected much later and generally with a much less severe outcome. However, if heterozygous GCD2 patients undergo laser‐assisted in situ keratomileusis (LASIK) surgery protein accumulation is accelerated and they develop massive protein accumulations a few years after surgery. Here, we present the protein profile of aggregate‐containing corneal tissue from GCD2 patients with a history of LASIK surgery using LC–MS/MS. Label‐free quantification of corneal extracellular matrix proteins showed accumulation of TGFBIp. This was supported by 2DE and immunoblotting against TGFBIp that revealed the accumulation of full‐length TGFBIp. In addition, a high molecular weight TGFBIp complex was more apparent in GCD2 patients after LASIK surgery, which may be important for the disease progression. Lastly, 2DE also revealed differential processing between GCD2 patients with a history of LASIK surgery when compared to healthy individuals.